Comparing Comprehensive Care and Departmental Clinical Education Models: Students' Perceptions at the University of Tennessee College of Dentistry. Issue 2 (1st February 2015) - Dehghan, Mojdeh; Harrison, Janet; Langham, Sue; Scarbecz, Mark; Amini, Mehdi
Abstract : In summer 2012, the University of Tennessee Health Science Center College of Dentistry transitioned from a departmental clinical education model to a comprehensive care/group leader model. The aim of this study was to investigate the perspectives of the fourth‐year class of dental students who, because the transition took place during their training, had experienced treating patients under both educational models. To achieve this objective, a questionnaire was designed to assess the students' opinions on the efficiency of their effort, availability of specialty faculty, stress, collaboration with classmates, and availability of exposure to different practice styles and techniques under the two systems. The students were also given an opportunity to provide open‐ended feedback on the shortcomings and advantages of the systems. The Class of 2013 had 81 students, 55 of whom participated in the survey for a response rate of 67.9%. The majority (86%) of the respondents preferred the comprehensive care model and reported feeling that, in it, they were able to accomplish more comprehensive dentistry with greater consistency of supervision from faculty in a more patient‐centered environment than in the departmental model. However, 56 percent considered having the same group leader for two years a disadvantage and recommended rotation of at least one group leader every six months. The results of this survey can help this college and other dental schools that are seeking to optimize their educational model to best serve students' educational experience and the dental needs of their patient population.